# Probably the hardest thing I ever did explained as simply as possible.

A while ago, I came across a situation where I needed to know things about some hidden state at compile time. Traditionally, this is done using *Hoare logic*. In Hoare logic, every statement has a precondition and a postcondition. That is, what must be true before the statement and what will be true after the statement. For the statement “set `x`

to `7`

”, the precondition is that `x`

exists, and the postcondition is that is `x = 7`

. We can chain multiple statements and get a final postcondition using the rules of Hoare logic.

Hoare logic is limited, which is one reason I strongly prefer (total) functional programming over imperative programming. Nevertheless, even functional programmers must deal with mutable state at some point. Generally we do this with a function of type

`-> s s `

where `s`

is the type of the state. That is, a function that takes as state as input, and produces a new state as output. A state-changing function may also return some value, so the actual type of the function is

`-> (a, s) s `

where `a`

is the type of the return value. In functional programming we use tuples to “return” multiple values. When we define how several state-changing functions can be chained together, they are called *monads*. You don’t need to understand what that means exactly. “Monad” is just a mathematical name for a certain pattern.

It seemed what I wanted was Hoare logic over state monads. I came across a paper about the Hoare state monad. With the knowledge I had, this was one of the most difficult things I have ever implemented. I had already given up on Hoare state monads at least twice. This time I finally managed it after a full week. I feel that not sharing this journey would be a waste. Especially since they will probably turn out to be too complicated for the purpose I had in mind.

The code in this article is what I actually used to deconstruct the problem for myself. Plus a few extras for things that are only obvious to me.

Not every language can express Hoare state monad, we will need a sufficiently powerful type system. I was using Idris 2, so this was not a problem. Don’t worry, I will go through any unusual concepts before using them.

First, let’s make our own state monad. I’m going to use a hardcoded state, usually this would be variable.

`data MyState = Foo | Bar`

For those unfamiliar with sum-types: the above declares that a value of type `MyState`

can be either `Foo`

or `Bar`

.

We go on to create a state monad for MyState, you might be unfamiliar with the notation so I will explain it afterward.

```
data MyStateMonad : a -> Type where
MkMyStateMonad : (MyState -> (a, MyState)) -> MyStateMonad a
```

Note that a single colon indicates a type declaration in Idris. E.g. `x : Int`

means “x is an integer”.

The first line, `data MyStateMonad : a -> Type where`

declares that the `MyStateMonad`

needs some `a`

as input to make a `Type`

. This is similar to arrays. In statically typed languages, we don’t have just “an array”, we have e.g. “an array of integers”. We must specify what’s “inside” it. Similarly we can have a state monad (think of it as a statement) that returns an integer `MyStateMonad Int`

, or a string `MyStateMonad String`

, or something else.

Below the data declaration are all the type’s constructors, only `MkMyStateMonad`

in this case. The constructor has certain arguments, `(MyState -> (a, MyState))`

in this case. Recall state-changing functions are `s->(a,s)`

, with `s=MyState`

in this case. The constructor also has a return type, `MyStateMonad a`

, which must match the type given in the data declaration header. The `a`

is variable in this context, but every `a`

must match, so the return type of the function defines what the type of `MyStateMonad a`

is. E.g.: for a function `f : MyState -> (Int, MyState)`

, we know `MkMyStateMonad f : MyStateMonad Int`

.

But what about input? Idris is a curried language, meaning we can have the function:

```
someFunction : Int -> Int
= (+) 1 someFunction
```

In other words, a function of type `MyState -> (a, MyState)`

can be a closure of as many arguments as you want.

State monads are useful as is. They let us use do-notation rather than less readable pattern matching:

```
do
<- actionA
x
actionB actionC x
```

vs.

```
\s1 =>
let
= actionA s1
(x, s2) = actionB s2
s3 in
actionC x s3
```

this is not what we set out to do though, so let’s talk about proofs in Idris.

You may have heard that types are propositions and values are proofs of propositions. The value `7`

is proof that `Int`

s exist. `7`

inhabits `Int`

. But we can do something a bit more interesting. Remember how `MyStateMonad`

needed some `a`

? We can do something similar with some other type over `a`

, say `P`

, so that `P a`

only holds for some `a`

. We do this by restricting what constructors are available.

A good example is the `Equal`

type:

```
data Equal : a -> b -> Type where
Refl : Equal x x
```

Here, we can use the `Refl`

constructor to prove `Equal x x`

, but there is no way to get an `Equal x y`

value. `Equal x y`

*is* a valid type, but there is no *value* of that type unless `x = y`

. Therefore, if you can pass a value with type `Equal x y`

to a function, you know within that function that `x = y`

. There are more complex cases, of course, such as restricting inputs to members of a list.

In the above example, `Equal`

is a *predicate*, `Equal x y`

is a *proposition*, and `Refl`

is a *proof* of `Equal x x`

.

We can use proofs in a function without adding runtime overhead:

```
acceptsOnlyFoo : (s1 : MyState)
-> {auto 0 prf : Equal Foo s1}
-> (Int, MyState)
= (7, Bar) acceptsOnlyFoo inState
```

Let’s dissect the function type line by line:

`(s1 : MyState)`

: this is similar to`MyState`

, but we have given the argument a name (`s1`

). In dependently typed programming, types can depend on values, so it’s useful to have value names in the type.`{auto 0 prf : Equal Foo s1}`

: the curly brackets make this argument implicit. We don’t have to specify it when calling the function, provided the compiler can figure it out itself. The`0`

means this argument will not exist at runtime.`auto`

denotes that the compiler will try to find a value for the type itself from the context.`prf`

is again the variable name and`Equal Foo s1`

is the type. In other words, we ask the compiler to find us some value of type`Equal Foo s1`

, with information known at compile time only. The compiler can only succeed in this by finding`Refl`

if it knows*for sure*the first argument is`Foo`

.`(Int, MyState)`

the output type as you are already familiar with.

This means we can call `acceptsOnlyFoo`

as:

`Foo acceptsOnlyFoo `

but not

`\x => acceptsOnlyFoo x`

unless we already know `Equal Foo x`

at compile time some other way.

You might be able to see where this is going now. If we have one function that implicitly requires `Equal Foo x`

, and another that “returns” an `Equal Foo x`

, those could be safely chained together.

While `acceptsOnlyFoo`

specifically requires a proof `Equal Foo`

, we do not want to limit ourselves to just proving equality. We need a more generic type for the precondition. A precondition could be any `MyState -> Type`

. A state monad with a precondition is therefore:

```
data MyPreconditionMonad : (pre : MyState -> Type) -> a -> Type where
MkMyPreconditionMonad :
: MyState) ->
( ( s1 auto 0 prf_pre : pre s1 } ->
{ MyState)
(a, ->
) MyPreconditionMonad pre a
```

Notice `{ auto 0 prf_pre : pre s1 }`

. The proof that must be found must be of type `pre s1`

. The initial state `s1`

is passed to it as argument at compile-time. Even though we don’t *really* know what it will be. In our previous example `pre`

was `Equal Foo`

.

An example of how to construct the state monad with precondition:

```
testPrecondition1 : MyPreconditionMonad (Equal Foo) Int
= MkMyPreconditionMonad acceptsOnlyFoo testPrecondition1
```

But what if we want to chain state monads that don’t have a precondition? We create a `Top`

proposition, which can always be satisfied:

```
data Top : a -> Type where
MkTop : Top a
```

Whatever `a`

we have, `MkTop`

will be proof that `Top a`

.

The name Top comes from formal logic, where it is indicated with the symbol ⊤. It shouldn’t actually take any arguments, but this servers our purpose well.

And this is how you might use it:

```
testPrecondition2 : MyPreconditionMonad Top Int
= MkMyPreconditionMonad f
testPrecondition2 where
f : (s1 : MyState) -> {auto 0 prf : Top s1} -> (Int, MyState)
= (7, s1) f s1
```

So that about covers preconditions. Postconditions are a little bit harder. As far as I know, Idris has no implicit results. Instead, we must return something like a tuple with an implicit argument. To do this we create a special type `PostS'`

. I’ve added the apostrophe because the actual `PostS`

will be a little different.

```
data PostS' : (s : Type) -> (s -> Type) -> Type where
MkPostS' : (val : s)
-> {auto 0 prf : prop val}
-> PostS' s prop
```

`PostS'`

is parametrized by a Type `s`

and a predicate about `s`

. Note that we pass `val`

to `prop`

, not `s`

, since `s`

is the type, and we want the proposition to hold about the value. For a concrete example, we want to be able to say `PostS' Int (Equal 7)`

, not `PostS' Int (Equal Int)`

.

Now let’s use `PostS'`

in a function that increases a counter by 1. The type of the counter will be `Nat`

, a built-in type for natural numbers:

```
testPostS' : (s1 : Nat) -> PostS' Nat (Equal (s1 + 1))
= MkPostS' (x+1) testPostS' x
```

As you can see, we don’t need to pass a proof, Idris has figured out `Equal (s1+1) (x+1)`

automatically, by unifying s1 and x. More or less. I think. Honestly I’m not that knowledgeable about how Idris searches for proofs.

But the real `PostS`

needs to be a bit more complex. We don’t just want the postcondition to be about the output state, it also needs to consider the returned value and input state. For instance we might want to declare that `s2 = s1 + x`

.

Luckily, if you understand the previous code, the next step is not particularly complicated:

```
data PostS : (a : Type) -> (s : Type) -> (a -> s -> Type) -> Type where
MkPostS : (val : a)
-> (state : s)
-> {auto 0 prf : prop val state}
-> PostS a s prop
```

A `MkPostS`

consists of a value, a state, and a proof that a proposition about said state and value holds (at compile time). You may have noticed that `prop`

takes no input state. That is because `PostS`

does not know about input state. If we want a predicate about input state, that input state must already be passed to it outside of PostS. For instance, if we want to express a resulting state is equal to the input state plus the returned values:

```
testPostS : (s1 : Nat) -> PostS Nat Nat (\n => Equal (s1 + n))
= MkPostS 7 (s1+7) testPostS s1
```

With that out of the way, let’s make a Hoare monad for a specific state. We will keep using `Nat`

now instead of `MyState`

, since there’s not much to prove about a `MyState`

:

```
data MyHoareMonad : (pre : Nat -> Type) -> (a : Type) -> (post : Nat -> a -> Nat -> Type) -> Type where
MkMyHoareMonad :
: Nat) ->
( ( s1 auto 0 _ : pre s1 } ->
{ PostS a Nat (post s1)
->
) MyHoareMonad pre a post
```

And we can use it as follows:

```
testMyHoareMonad : MyHoareMonad (Equal 0) Nat (\s1 => Equal)
= MkMyHoareMonad f
testMyHoareMonad where
f : (s1 : Nat) -> {auto 0 prf : Equal 0 s1} -> PostS Nat Nat (Equal)
= MkPostS{prf=Refl} (inState+1) (inState+1) --{prf=Refl} is needed here because of a compiler bug. f inState {prf}
```

Unfortunately there currently appears to be a bug in Idris’ auto strategy. It means that, for now, we won’t be able to rely on `auto`

as much. It’s not a huge deal provided it will get fixed in the future, but a tad annoying.

But it’s time for the real thing, make a Hoare state monad without hardcoded state type:

```
data HoareStateMonad : (s : Type) -> (pre : s -> Type) -> (a : Type) -> (post : s -> a -> s -> Type) -> Type where
MkHSMonad :
: s ) ->
( ( s1 auto 0 prf : pre s1 } ->
{ PostS a s (post s1)
->
) HoareStateMonad s pre a post
```

it’s not much different, we just replaced `Nat`

with a variable type `s`

.

Unfortunately, the hardest part is still to come. We want to use a Hoare state monad as a monad, or sort-of a monad. Technically we won’t be making a monad. A monad requires the rule `m m a -> m a`

, but since our “`m`

” has been decorated with pre- and postconditions, every “`m`

” in that formula would be different. Doesn’t really matter for us though, it’s close enough.

We need to define a `pure`

and a `>>=`

(bind) function.

A `pure`

function lifts a value to a monadic value, like making a list with a single element, doing a no-op, or, in the case of a regular state monad, leave the state unchanged and return the lifted value:

```
pure : a -> MyStateMonad a
= MkMyStateMonad ((,) val) pure val
```

So what should the pre- and postconditions be for `pure`

? Since we’re not using the state in any way, the precondition can just be `Top`

. Anything goes.

We could also use `Top`

as the postcondition, but that would lose some useful information. We know the input state is equal to the output state (`Equal s1 s2`

), and the output value is equal to the lifted value. We can use a tuple as a conjunction to indicate to predicates must both hold. After all, we must be able to provide *both* values of a tuple to construct it.

With that, `pure`

becomes:

```
pure : (a1 : a) -> HoareStateMonad s Top a (\s1, a2, s2 => (Equal s1 s2, Equal a1 a2))
= MkHSMonad $ \s1 => MkPostS a1 s1 pure a1
```

And now for the tricky bit, the bind operator.

For regular state monads, the bind operator chains the state-changing functions together:

```
(>>=) : MyStateMonad a -> (a -> MyStateMonad b) -> MyStateMonad b
>>=) (MkMyStateMonad f1) act2 = MkMyStateMonad $ \s1 =>
(let
= f1 s1
(val1, s2) MkMyStateMonad f2) act2 val1
(in
f2 s2
```

So what we’re really doing, is first executing action A, the executing action B, potentially using A’s output. I will be using a notation from program algebra for clarity: `A ; B`

means “first do A, then do B”.

But, again, what should the pre- and postconditions be? Let’s first look at the part of bind’s type signature we do know:

```
(>>=) : HoareStateMonad s p1 a q1
-> ((x : a) -> HoareStateMonad s (p2 x) b (q2 x))
-> HoareStateMonad s ?p3 b ?q3
```

Here, `s`

is the state type, `p1`

is the precondition of action A, `a`

is the return type of action A, `q1`

is the postcondition of action A, and `x`

is the input to action B. `p2`

and `q2`

are a bit different than `p1`

and `q1`

. They are applied not just over input state, return value and output state, but also over the input value `x`

. Why? Consider the following function:

```
trySetState : (x : Nat) -> (s1 : Nat) -> (Bool, Nat)
=
trySetState x s1 if (someCondition)
then (True, x)
else (False, s1)
```

The function sets the state based on some condition. This is a common pattern. A reasonable postcondition for `trySetState`

would express that if the return type is `True`

, then `Equal x s2`

is proven, and if it is `False`

, then `Equal s1 s2`

is proven. Declaring this proposition requires using `x`

as input.

As the example shows, it is useful to also consider inputs in the pre- and postconidtion for the second argument of `bind`

.

Back to the bind operation. What is `p3`

, the precondition of the “first A then B”? Since A executes first, `p3`

must contain `p1`

. Furthermore, to satisfy `p2`

, `p3`

must ensure that `p2`

holds after A has executed, so the postcondition `q1`

of A must imply the precondition `p2`

of B. Remember also that the type of `p3`

is `s -> Type`

.

We define a function `bind_pre`

that constructs a new precondition from `p1`

, `q1`

and `p2`

:

```
bind_pre: {s : Type}
-> {a : Type}
-> (p1 : s -> Type)
-> (q1 : s -> a -> s -> Type)
-> (p2 : a -> s -> Type)
-> s -> Type
=
bind_pre p1 q1 p2 s1
( p1 s1: a} -> {s2 : s} -> q1 s1 x s2 -> p2 x s2
, {x )
```

This isn’t easy, so let’s go through it line by line:

`bind_pre`

: the function name`: {s : Type}`

: the type declaration for an implicit argument. You can read this as “for any`s`

that is a type”`-> {a : Type}`

: Read as “for any`a`

that is a type”`-> (p1 : s -> Type)`

: first argument to the function (not counting implicits). A predicate over`s`

. The precondition of the first action.`-> (q1 : s -> a -> s -> Type)`

: Postcondition of the first action`-> (p2 : a -> s -> Type)`

: precondition of the second action. Based on the output of the first action.`-> s -> Type`

: The return type. Remember`p3`

must be`s -> Type`

. Idris is curried to`x -> s -> Type`

and`x -> (s -> Type)`

are exactly the same thing.`bind_pre p1 q1 p2 s1 =`

: begin of function body. We give the arguments new names here, that is because the names in the type declaration are only valid within that type declaration. I used matching names for clarity.`( p1 s1`

: The result is a tuple, with as first value the regular precondition of the first action.`, {x : a} -> {s2 : s} -> q1 s1 x s2 -> p2 x s2`

: for any`x`

of type`a`

, and any`s2`

of type`s`

, if we can prove`q1 s1 x s2`

, then we must also be able to prove`p2 x s2`

.

Well, that was hard enough, but the postcondition is worse. `q1`

and `q2`

are qualified on intermediate results. These intermediate values won’t appear in the resulting monad’s type declaration. We only know that they exist and that the postconditions hold for them. We’re going to need a function for existential quantification:

```
exists : {p : _} -> (p -> Type) -> Type
= {b : Type} -> ({a : _} -> f a -> b) -> b exists f
```

What we did here, is reverse universal quantification to get existential qualification. `{a : Type} -> a -> Type`

is a predicate that works *for all* `a`

s that are `Type`

s. `Top`

is such a predicate. Conversely, we want to state that some `a`

*exists* that satisfies a certain predicate. There is a duality here: if all you know is that something *exists*, you can only reason about it using predicates that work *for all* values. In programming, that means an existentially quantified ouput is mathematically the same as a universally quantified continuation. In other words: `exists x. x`

is the same as `forall y . (forall x . x -> y) -> y`

. The latter can be read as “you can prove any statement of type `y`

so long as you can prove it using any statement of type `x`

”. Since we know nothing about `y`

, only that it can be proven using any `x`

, this tells us that some `x`

must exist. The other way works too: if we know some `x`

exists, we know that a `y`

can be proven if it can be proven for any `x`

.

Now finally we can get to the postcondition of `A; B`

.

Remember that `q1`

and `q2`

are qualified over intermediate values, of which we only know they exist in the type signature. We therefore have:

```
bind_post: {s : Type}
-> {a : Type}
-> {b : Type}
-> (q1 : s -> a -> s -> Type)
-> (q2 : a -> s -> b -> s -> Type)
-> (s -> b -> s -> Type)
bind_post q1 q2 s1 y s3= exists (\x => exists (\s2 => (q1 s1 x s2, q2 x s2 y s3)))
```

Which leaves the final declaration of bind, I’ll explain it line-by-line later:

```
(>>=) : {a : Type}
-> {b : Type}
-> {s : Type}
-> {p1 : s -> Type}
-> {q1 : s -> a -> s -> Type}
-> {p2 : a -> s -> Type}
-> {q2 : a -> s -> b -> s -> Type}
-> HoareStateMonad s p1 a q1
-> ((x : a) -> HoareStateMonad s (p2 x) b (q2 x))
-> HoareStateMonad s (bind_pre p1 q1 p2) b (bind_post q1 q2)
>>=) (MkHSMonad f1) act2 = MkHSMonad f
(where
f : ( s1 : s )
-> { auto 0 pre3 : bind_pre p1 q1 p2 s1 }
-> PostS b s (bind_post q1 q2 s1)
=
f s1 {pre3} let
MkPostS v1 s2 {prf=post1} = f1 s1
MkHSMonad f2 = act2 v1
MkPostS v2 s3 {prf=post2} = f2{prf= (snd pre3) post1} s2
in MkPostS v2 s3 {prf=(\e1 => (e1 $ \e2 => e2 (post1, post2)))}
```

`{a : Type}`

: implicit argument. Read as “for all`a`

s that are types”`{b : Type}`

: for all`b`

s that are types`{s : Type}`

: for all`s`

s that are types`{p1 : s -> Type}`

: for all predicates`p1`

about an`s`

(this is the type of our first precondition)`{q1 : s -> a -> s -> Type}`

for all predicates`q1`

about an`s`

,`a`

and another`s`

(the type of our first postcondition)`{p2 : a -> s -> Type}`

: for all predicates`p2`

over`a`

and`s`

(second precondition, extra qualified over the input)`{q2 : a -> s -> b -> s -> Type}`

: second postcondition`HoareStateMonad s p1 a q1`

: the first argument, a`HoareStateMonad`

about state`s`

, with precondition`p1`

, return value`a`

, and postcondition`q1`

.`((x : a) -> HoareStateMonad s (p2 x) b (q2 x))`

: the second argument, a function that takes an`a`

(with value`x`

), and yields a`HoareStateMonad`

about state`s`

, with precondition`p2 x`

, returning a`b`

, and with postcondition`q2 x`

`HoareStateMonad s (bind_pre p1 q1 p2) b (bind_post q1 q2)`

: results in a`HoareStateMonad`

about state`s`

, with precondition`bind_pre p1 q1 p2`

, returning a value`b`

, and with postcondition`bind_post q1 q2`

And for the function body:

`(>>=) (MkHSMonad f1) act2 = MkHSMonad f`

: unwrapping and wrapping the state-changing functions in monad constructors.`f`

is the new state-changing function we create as the sequence of our inputs.`f : ( s1 : s )`

: the first argument to the new function is the input state`-> { auto 0 pre3 : bind_pre p1 q1 p2 s1 }`

: we also require a proof that the combined preconditions hold`-> PostS b s (bind_post q1 q2 s1)`

: and produce a value with suitable postconditions`f s1 {pre3} =`

: we note the precondition proof`pre3`

explicitely as we will need to use it manually in the function body.`MkPostS v1 s2 {prf=post1} = f1 s1`

: “Run” the first action with the input state. This will result in a return value`v1`

, a new state`s2`

and an proof of the postcondition`post1`

. Note that`post1`

still has multiplicity 0 so it will not exist at runtime.`MkHSMonad f2 = act2 v1`

: pass the return value of the first action, this will result in a new state-changing function`f2`

, wrapped in a HoareStateMonad.`MkPostS v2 s3 {prf=post2} = f2{prf= (snd pre3) post1} s2`

: we “run”`f2`

with state`s2`

, but must also prove its precondition. The precondition`pre3`

is`( p1 s1 , {x : a} -> {s2 : s} -> q1 s1 x s2 -> p2 x s2 )`

The second argument is of interest here, and we have`q1 s1 v1 s2`

from`post1`

, and so`(snd pre3) post1`

is proof of`p2 v1 s2`

.`MkPostS v2 s3 {prf=(\e1 => (e1 $ \e2 => e2 (post1, post2)))}`

: we create a return value with postcondition, but must provide proof of our new postcondition. Recall existential types are continuations, and so we create a continuation as proof.

## Next steps

I still have to use `HoareStateMonads`

in practice. I planned to use them to reduce what mistakes can be made when writing a WebGL program. Those can be very tricky to debug. I fear `HoareStateMonads`

require passing around proofs far too much to be useful in most cases. The extra programming work might not weigh up against the reduction of bugs. But perhaps Idris will be able to find many proofs by itself. Or perhaps I will need a different data type entirely.

If you like my work, please consider buying me a coffee.